DETERMINAN NILAI INFORMASI PELAPORAN KEUANGAN DAERAH STUDI PADA SKPK KABUPATEN PIDIE - Nuranda, Weni; Fahlevi, heru (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this study is to examine the effect of human resource capacities, information technology utilization, accounting internal control and local government financial monitor on information value of local government financial reporting.The popullation in this study is 38 Working Units (or Satuan Kerja Perangkat Kabupaten/SKPK) in kabupaten Pidie. This study involved all the SKPK as research sample. Data was collected through questionnaires that distributed and filled by two respondents from each SKPK i.e. Financial Administration Officers (or Pejabat Penatausahaan Keuangan/PPK) and Accounting Staffs. Multiple regression method was used to analyses the collected data. This study confirms that human resource capacities, information technology utilization, accounting internal control and local government financial monitor determine the information value of regional government financial reporting of SKPK Kabupaten Pidie both individually and collectively.